The effectiveness of library service by implementing Kumpulan Inovatif Kreatif (K.I.K) at Tun Dr. Ismail Library (PTDI)/ Muhammad Helmirrul Ariffin - Ariffin, Muhammad Helmirrul (2014)
This research is about the Effectiveness of Library Services by Implementing Kumpulan Inovasi Kreatif (K.I.K) at PTDI. The scope of this research is to examine the student awareness about K.I.K activity in PTDI. It also determine about the student perception towards PTDI library services after implementing the K.I.K activity and its- benefit for the staff -innovation-- and creativity.